2015
DOI: 10.1124/mol.114.097204
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological NAD-Boosting Strategies Improve Mitochondrial Homeostasis in Human Complex I–Mutant Fibroblasts

Abstract: Mitochondrial disorders are devastating genetic diseases for which efficacious therapies are still an unmet need. Recent studies report that increased availability of intracellular NAD obtained by inhibition of the NAD-consuming enzyme poly(ADP-ribose) polymerase (PARP)-1 or supplementation with the NAD-precursor nicotinamide riboside (NR) ameliorates energetic derangement and symptoms in mouse models of mitochondrial disorders. Whether these pharmacological approaches also improve bioenergetics of human cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…NA helped decrease the amount of ROS in the worms system and it was suggested that the NA increased NAD + pools which can help maintain Sirt3 acetylation patterns. Nicotinamide riboside can also increase the NAD + pool without activating Sirt3, but providing comparable benefits [222]. PARP-1inhibitors, Phe and PJ34, demonstrated improved mitochondrial content and membrane potential in Complex I mutant human fibroblasts [222].…”
Section: Mitochondrial Targeted Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…NA helped decrease the amount of ROS in the worms system and it was suggested that the NA increased NAD + pools which can help maintain Sirt3 acetylation patterns. Nicotinamide riboside can also increase the NAD + pool without activating Sirt3, but providing comparable benefits [222]. PARP-1inhibitors, Phe and PJ34, demonstrated improved mitochondrial content and membrane potential in Complex I mutant human fibroblasts [222].…”
Section: Mitochondrial Targeted Therapiesmentioning
confidence: 99%
“…Nicotinamide riboside can also increase the NAD + pool without activating Sirt3, but providing comparable benefits [222]. PARP-1inhibitors, Phe and PJ34, demonstrated improved mitochondrial content and membrane potential in Complex I mutant human fibroblasts [222]. Both inhibitors increase the transcription of mitochondrially encoded respiratory complexes, relaying a better survival of the cells.…”
Section: Mitochondrial Targeted Therapiesmentioning
confidence: 99%
“…The only clinical result so far comes from the NAD + precursor acipimox, which improves muscle mitochondrial function and glucose homeostasis in type 2 diabetes patients (van de Weijer et al 2015). In the field of IEM, NR was shown to restore mitochondrial homeostasis in fibroblasts from patients with a mitochondrial respiratory chain defect (Felici et al 2015). Furthermore, NR induces mitochondrial biogenesis in skeletal muscle of mice that suffer from mitochondrial myopathy (Khan et al 2014) and induces OXPHOS-related gene expression and improves motor performance in mice that suffer from cytochrome c oxidase deficiency (Cerutti et al 2014).…”
Section: Pharmacological Sirtuin Activation To Treat Inborn Errors Ofmentioning
confidence: 99%
“…Additionally, NR was reported to elevate NAD + levels and protect against two distinct models of mitochondrial disease in mice (235,236). These studies have recently been expanded to human cells; NR delivery and PARP inhibition were reported to restore mitochondrial membrane potential and oxidative activity in human fibroblasts (237). Mitochondrial dysfunction is a hallmark of aging and effective energy metabolism is essential to support repair responses during oxidative insults.…”
Section: Nicotinamide Riboside Supplementationmentioning
confidence: 99%
“…NR delivery is an emerging intervention to combat this NAD + deficiency. Current literature has reported that NR will elevate NAD + levels to promote mitochondrial health and protect against metabolic disease (233)(234)(235)(236)(237). Some reports have indirectly linked NR to oxidative stress response and DNA damage repair pathways in diseased mouse models (238,239).…”
Section: Nicotinamide Riboside Supplementationmentioning
confidence: 99%